2006
DOI: 10.1177/0095798406290552
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Suicidal Behaviors in the African American Community

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Further, more published research is available on risk factors of African American youth suicidality than on protective factors, thus emphasizing a more negative perspective with this population, rather than the more resiliencybased framework of protective factors [11]. Identifying protective factors that may attenuate suicide risk behavior for African American youth remains understudied [21,22].…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, more published research is available on risk factors of African American youth suicidality than on protective factors, thus emphasizing a more negative perspective with this population, rather than the more resiliencybased framework of protective factors [11]. Identifying protective factors that may attenuate suicide risk behavior for African American youth remains understudied [21,22].…”
Section: Previous Researchmentioning
confidence: 99%
“…Protective factors were more generalized (i.e., not tailored to youth) and there was no specific mention of socioeconomic status of the samples in the reviewed studies [18]. Crosby and Molock conducted a review of the history of suicide research in African American communities, which included predominantly risk factor literature, with some focus on protective factors for adolescent suicide [11]. Balis and Postolache conducted a literature review of risk and protective factors across five ethnic groups of adolescents, including African Americans [1].…”
Section: Previous Researchmentioning
confidence: 99%
“…Research indicates that no other group of men or women from any other racial or ethnic background exhibit comparatively high levels of spiritual practices as African American women (Pew Forum US Religious Landscape Survey, 2008). It has even been suggested that the substantially lower rates of completed suicide in African American females, compared to African American males, may be related to African American women engaging in more protective behaviors including spiritual practices (Griffin-Fennell & Williams, 2006; Utsey, Hook, & Stanard, 2007)…”
Section: Introductionmentioning
confidence: 99%
“…Nos Estados Unidos, dentre adolescentes negros e negras de 15 a 29 anos, suicídio chega a ser a terceira causa de morte. 36 A desproporção entre a porcentagem de pacientes negros nos Centros de Saúde com relação aos CAPS também pode ser justificada por essa associação (raça e saúde mental).…”
unclassified